Expression of a Human Prostatic Acid Phosphatase (PAP)-IgM Fc Fusion Protein in Plants Using In vitro Tissue Subculture - Kang, Yang J.; Kim, Deuk-Su; Myung, Soon-Chul; Ko, Kisung (Frontiers in Plant Science, 2017)
In this study, prostatic acid phosphatase (PAP), which is overexpressed in human prostate cancer cells, was cloned to be fused to the IgM constant fragment (Fc) for enhancing immunogenicity and expressed in transgenic tobacco plants. Then, the transgenic plants were propagated by in vitro tissue subculture. Gene insertion and expression of the recombinant PAP-IgM Fc fusion protein were confirmed in each tested the first, second, and third subculture generations (SG1, SG2, and SG3, respectively). Transcription levels were constantly maintained in the SG1, SG2 and SG3 leaf section [top (T), middle (M), and base (BA)]. The presence of the PAP-IgM Fc gene was also confirmed in each leaf section in all tested subculture generations. RNA expression was confirmed in all subculture generations using real-time PCR and quantitative real-time PCR. PAP-IgM Fc protein expression was confirmed in all leaves of the SG1, SG2, and SG3 recombinant transgenic plants by using quantitative western blotting and chemiluminescence immunoassays. These results demonstrate that the recombinant protein was stably expressed for several generations of in vitro subculture. Therefore, transgenic plants can be propagated using in vitro tissue subculture for the production of recombinant proteins.